2012
DOI: 10.1523/jneurosci.2249-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Necessary, Sufficient and Permissive: A Single Locomotor Command Neuron Important for Intersegmental Coordination

Abstract: In this report we posed the over-arching question: What multiple contributions can a single neuron have on controlling the behavior of an animal, especially within a given context? To address this timely question, we studied the neuron R3b-1 in the medicinal leech. This bilaterally paired neuron descends from the cephalic ganglion and projects uninterrupted through the segmental ganglia comprising the nerve cord; its terminal arbors invade each hemi-ganglion. We discovered that a single R3b-1 neuron functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…For example, brainstem neurons provide commands to locomotor central pattern generators (CPGs) in the spinal cord (Dubuc et al, 2008;Roberts et al, 2008;Kiehn, 2016). Similarly, in invertebrates, commands for locomotion and feeding come from neurons outside of the CPG and often in other ganglia (Gillette et al, 1982;Gamkrelidze et al, 1995;Panchin et al, 1995;Frost and Katz, 1996;Stein, 2009;Puhl et al, 2012). Here, we show that the hierarchical position of a neuron differs in two species even though the neuron is involved in the production of the same behavior in those species.…”
Section: Introductionmentioning
confidence: 69%
“…For example, brainstem neurons provide commands to locomotor central pattern generators (CPGs) in the spinal cord (Dubuc et al, 2008;Roberts et al, 2008;Kiehn, 2016). Similarly, in invertebrates, commands for locomotion and feeding come from neurons outside of the CPG and often in other ganglia (Gillette et al, 1982;Gamkrelidze et al, 1995;Panchin et al, 1995;Frost and Katz, 1996;Stein, 2009;Puhl et al, 2012). Here, we show that the hierarchical position of a neuron differs in two species even though the neuron is involved in the production of the same behavior in those species.…”
Section: Introductionmentioning
confidence: 69%
“…Filled circles indicate inhibitory interactions; filled arrowheads with plus signs indicate excitatory interactions. DA indicates bath-application of dopamine; the X indicates that DA inhibits the pathway to the swim CPG; the DA also activates the crawl CPG (Puhl et al, 2012). Modified from Esch et al has no impact on the CS (an effect not shown in Fig.…”
Section: Swim Oscillator Interneuronsmentioning
confidence: 99%
“…Caenorhabditis elegans also uses dopamine and serotonin to set the balance between these two locomotory behaviors (Vidal-Gadea et al, 2011). Recently it has been discovered that, in the leech, systemically applied dopamine induces R3b1 to burst in a manner consistent with crawling and constrains the entire central nervous system to crawl only (never swim) when R3b1 is electrically stimulated (Puhl et al, 2012). A strategy of employing neuromodulators to encode an environmental context that would naturally be relatively unchanging, such as water depth, would be consistent with our observation [also seen by Esch et al ] that leeches poke their heads above water when first introduced to a new environment (and only occasionally after that).…”
Section: Swim Oscillator Interneuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biogenic amine modulators like dopamine and serotonin, which act at both the segmental and cephalic levels, predictably influenced the type of locomotion expressed in isolated CNS preparations. Finally, signaling from a multifunctional identified descending cephalic neuron onto cells housed in the segmental ganglia (named R3b-1) is both necessary and sufficient for crawling but only activates and modulates swimming (it is not necessary for swimming; Puhl et al 2012). These results and others like them have inspired new projects where investigators are probing how higher-order, decision-making cephalic neurons interact with segmental locomotor circuits as well as how neuromodulators influence their interactions.…”
Section: Circadian Rhythms and Clock Genesmentioning
confidence: 99%